Managing sales return in dual sales channel: its product substitution and return channel analysis. (16th September 2011) - Widodo, Erwin; Takahashi, Katsuhiko; Morikawa, Katsumi; Pujawan, I. Nyoman; Santosa, Budi
Although many efforts have been devoted to exploring dual sales channel (DSC) financial performance, the issue of managing its sales return is still lacking attention. Mismanagement in such online return handling may threaten channel profitability. Therefore, we propose three scenarios. First, the benchmark scenario is a lost-sales consideration model. The second one is an online facility return scenario, which represents the availability of an online facility to provide product substitution. In accommodating online customer preference to return the product through a conventional store, a conventional store return scenario is also prepared as the third scenario. The first two scenarios cope with the importance of product substitution; meanwhile, the second and the third ones examine the selection of the sales return channel. By analysing the equilibrium values of the total and partial profits given by channel prices as the primary decision variables under Bertrand and Stackelberg schemes, some beneficial insights for managing a DSC by considering its sales return are provided.